Pelaksanaan Sasaran Keselamatan Pasien Berdasarkan Standar Nasional Akreditasi Rumah Sakit Edisi 1 Di RSUD Kota Yogyakarta - Totok Sundoro; Aisah Barkah Rahaded; Ilfia Zitri; Marlina Agustina; Zakiyatul Fatihah; Nur Miliarti Karimah (Jurnal Admmirasi, 2019)
RSUD Kota Yogyakarta has not implemented the National Standards for Hospital Accreditation (SNARS) 1ST Edition. The results of implementing patient safety targets in RSUD Kota Yogyakarta based on SNARS 1ST Edition are still not implemented properly. Research Objectives To find out the description (regulation, implementation, barriers, and recommendation) regarding the fulfillment of patient safety goals in RSUD Kota Yogyakarta. Qualitative research with case study research design (case study). The research subjects were hospital management, hospital staff and patients. The Object of Research is the Implementation of Hospital Patient Safety Goals in the SNARS 1ST Edition. The validity of the data using triangulation techniques. Regulation of the implementation of 6 patient safety targets has been made, Implementation of patient safety goals in RSUD Kota Yogyakarta has been fulfilled completely with a score of 100%. The obstacle faced by officers/staff in the implementation is the Director's Policy which does not yet contain the application of safe surgical checklists in the Outpatient Installation, especially in the dental and oral surgery, some supporting facilities such as real hand that have not all been installed; identity labels were never available, and hand rub for each patient bed, patient safety culture for officers in providing information about reasons and benefits when installing identity bracelets; There is a difference in the number of critical values ​​between the laboratory and the pediatrician. The policy for 6 patient safety targets in hospitals has been well implemented. The recommendation that needs to be done is hospital management to complete the contents of the policy that has not been made and complete the supporting infrastructure that has not been fulfilled.